Brazilian kefir fraction mitigates the Alzheimer-like phenotype in Drosophila melanogaster with β-amyloid overexpression model - Serena Mares Malta; Tamiris Sabrina Rodrigues; Matheus Henrique Silva; Alexandre Souza Marquez; Rafael Bernardes Ferreira; Fernanda Naves Araújo do Prado Mascarenhas; Renata Graciele Zanon; Lucas Matos Martins Bernardes; Letícia Leandro Batista; Murillo Néia Thomaz da Silva; Débora de Oliveira Santos; Ana Carolina Costa Santos; et al. (Scientific Reports)
Abstract Alzheimer’s disease (AD) is a progressive neurodegenerative condition and the primary form of dementia among elderly people. The amyloidogenic hypothesis is the main theory that explains this phenomenon and describes the extracellular accumulation of amyloid beta (Aβ) peptides. Model organisms such as Drosophila melanogaster have been utilized to improve the understanding of this disease and its treatment. This study evaluated the effects of peptide and metabolic fractions of Brazilian kefir on a strain of D. melanogaster that expresses human Aβ peptide 1–42 in the eye. The parameters assessed included ommatidial organization, vacuole area, retinal thickness, and Aβ peptide quantification. The present study revealed that the fractions, particularly the peptidic fraction, significantly reduced the vacuole area and increased the retina thickness in treated flies, indicating an improvement in neurodegeneration phenotype. The peptidic fraction was also found to alter Aβ aggregation dynamics, inhibiting Aβ fibril formation, as revealed by dynamic light scattering. This study demonstrated that kefir fractions, particularly the peptidic fraction < 10 kDa, have the potential to regulate Aβ aggregation and alleviate neurodegeneration in a Drosophila melanogaster AD-like model. These findings suggest that kefir fractions could be viable for the bioprospection of novel drug prototypes for AD treatment, providing valuable insights into strategies targeting Aβ aggregation and neurodegeneration in AD.